Answer: 3x-y=2 and 3x-y=1 (First Answer Choice)
First you want to isolate the y. (Subtraction Property of Equality)
-y = -3x+2 -y = -3x + 1
Then, extract the negative from the y by dividing by -1. (Division Property of Equality and Distribute)
(-1)-y = (-1)(-3x + 2) (-1)-y = (-1)(-3x + 1)
y = 3x - 2 y = 3x - 1
Notice that if you do the steps for the other answer choices, you would end up with a negative slope, which is not presented in the picture. A negative slope goes up down and positive slip goes down up.